Genome wide association study on early puberty in Bos indicus - Nascimento, A. V.; Matos, M. C.; Seno, L. O.; Romero, A. R. S.; Garcia, J. F. [UNESP]; Grisolia, A. B. (Funpec-editora, 2016)
The aim of this study was to evaluate a genome wide association study (GWAS) approach to identify single nucleotide polymorphisms (SNPs) associated with fertility traits (early puberty) in Nellore cattle (Bos indicus). Fifty-five Nellore cows were selected from a herd monitored for early puberty onset (positive pregnancy at 18 months of age). Extremes of this phenotype were selected; 30 and 25 individuals were pregnant and non-pregnant, respectively, at that age. DNA samples were genotyped using a high-density SNP chip (> 777.000 SNP). GWAS using a case-control strategy highlighted a number of significant markers based on their proximity with the Bonferroni correction line. Results indicated that chromosomes 5, 6, 9, 10, and 22 were associated with the traits of interest. The most significant SNPs on these chromosomes were rs133039577, rs110013280, rs134702839, rs109551605, and rs41639155. Candidate genes, as well as quantitative trait loci (QTL) previously reported in the Ensembl and Cattle QTLdb databases, were further investigated. Analysis of the regions close to the SNP on chromosomes 9 and 10 revealed that four QTL had been previously classified under the reproduction category. In conclusion, we have identified SNPs in close proximity to genes associated with reproductive traits. Moreover, U6 spliceosomal RNA was present on three different chromosomes, which is possibly associated with age at first calving, suggesting that it might be a strong candidate for future studies.
Keywords: Bos indicus; GWAS; U6 spliceosomal RNA; Early puberty